Vocational Orientations of Senior Female Students of Higher Religious Education: The Sample of Firat University - Karateke, Tuncay; Tüken, Yunus (My University, 2025)
The purpose of this study is to reveal the post-graduation career orientations of senior female students of higher religious education. The quantitative study was conducted using a descriptive survey model. The sample consisted of 191 female students in their final year at the Faculty of Theology at Fırat University who voluntarily participated in the study. The data ofthe study were obtained through a two-part questionnaire developed by the researchers after reviewing the relevant literature and consulting with experts. The data obtained were analyzed using the SPSS software package in terms of frequency (f) and percentage (%) and presented in tables. According to the results, it was determined that 92.1% of female students in their final year at the Faculty of Theology wanted to work after graduation, while 7.9% had not yet decided whether to work after graduation. It was found that 64.8% of female students wanted to become teachers of Religious Culture and Ethics Course, 8.1% wanted to become Quran course instructors, 7.1% wanted to become academics, and 5.1% had not yet decided on the profession they wanted to pursue after graduation. The study revealed that senior female students pursuing higher religious education do not show interest in professions within the Presidency of Religious Affairs. It was determined that 53.9% of these students stated that compatibility with their beliefs was an influential factor in their career choice, while 34% believed that compatibility with their gender was influential. Additionally, 67.5% of female students in their final year believed that injustices or difficulties in the examination system posed obstacles to achieving their career goals. Furthermore, 70.7% of female students believed that they would obtain their preferred profession after graduation, and 80% stated that if they failed to obtain their preferred profession in the first year, they would prepare again to achieve it. The study also revealed that more than half of the students (68.6%) believed they would graduate from the Faculty of Theology with at least some of the necessary skills for their chosen profession. Finally, it was concluded that although students considered gender an important factor in their career choices, they believe it will not create disadvantages in their future professional lives.
Keywords: Religious Education; Career Choice; Faculty of Theology; Female Students; Vocational Orientation